2022
DOI: 10.18332/tid/144622
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum cotinine and α-Klotho levels among adults: Findings from the National Health and Nutrition Examination Survey 2007–2016

Abstract: INTRODUCTION Serum cotinine is a sensitive and specific marker of tobacco smoke exposure. α-Klotho is an anti-ageing molecule, which plays an important role in several diseases. We aimed to examine the association between smoke exposure indicated by the serum cotinine and α-Klotho levels, as previous reports regarding the level of α-Klotho in smokers have been inconsistent. METHODS This secondary dataset analysis included 9833 participants (aged 40–79 years; 47.0% femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…Furthermore, another study based on a small sample of sedentary and healthy men (n = 22) found, interestingly, that moderate-intensity training, as opposed to sprint-intensity training, increased serum Klotho concentrations 31 . Yao et al analyzed the NHANES database data from 2007 to 2016 and found a signi cant threshold effect between serum cotinine and serum α-Klotho levels 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study based on a small sample of sedentary and healthy men (n = 22) found, interestingly, that moderate-intensity training, as opposed to sprint-intensity training, increased serum Klotho concentrations 31 . Yao et al analyzed the NHANES database data from 2007 to 2016 and found a signi cant threshold effect between serum cotinine and serum α-Klotho levels 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In subgroup analyses, the p -value for the interaction between smoking and race on serum α-klotho levels was less than 0.001. Racial disparities may be linked to variations in tobacco brand preferences, smoking intensity, pharmacokinetics influenced by cytochrome P450 (CYP2A6) enzyme activity, and smoking habits [ 27 ]. The exact mechanism is unclear and needs to be further explored in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, the following covariates were included in this study: age, sex, race/ethnicity, body mass index (BMI) [ 24 , 25 ], alcohol status [ 26 , 27 ], hypertension [ 28 , 29 ], diabetes [ 12 , 30 ], stroke [ 31 , 32 ], liver disease [ 33 , 34 ], CVD (coronary heart disease, angina, or congestive heart failure) [ 5 , 13 ], CKD [ 35 , 36 ], chronic obstructive pulmonary disease (COPD) [ 37 , 38 ], and cancer [ 14 , 39 ]. The race/ethnicity categories consisted of non-Hispanic White, non-Hispanic Black, Mexican American, and other races.…”
Section: Methodsmentioning
confidence: 99%
“…Serum cotinine is a specific marker of smoking and reflects exposure to nicotine. The levels of klotho decrease as smoke exposure increases, then it reaches a tipping point where klotho levels start to increase [102]. Further research on the effect of cigarette use on klotho levels is needed.…”
Section: Tobaccomentioning
confidence: 99%